2023
DOI: 10.3389/fphar.2023.1255752
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between anesthesia and melatonin: a review

Rui Guo,
Junming Ye,
Baozhen Liao
et al.

Abstract: Introduction: This comprehensive review delves into the intricate and multifaceted relationship between anesthesia and melatonin, aiming to provide essential insights for perioperative clinical anesthesiologists and stimulate interest in related research. Anesthesia and surgery have the potential to disrupt melatonin secretion, leading to sleep disorders, postoperative neurocognitive dysfunction and other symptoms. In comparison to previous reviews, this review provides a comprehensive summary of the various a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…1,2 Causes of these disturbances are multifactorial and may involve pain, postsurgical inflammation, personnel disturbances, and heightened awareness in unfamiliar environments. 1 Additionally, general anesthesia may contribute to postoperative sleep impairments, which likely result from circadian rhythm shifts as controlled by the body’s hypothalamic SCN, or “master clock.” 2,8,12 Through a gamma-aminobutyric acid (GABA)-mediated inhibitory effect, propofol has been shown to impair circadian rhythm generation and decrease endogenous melatonin secretion. 2,8,13 It has also been shown that the neural oscillatory (electroencephalogram) dynamics produced by medication-induced activation of GABAergic neurons differ from those produced by natural sleep.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Causes of these disturbances are multifactorial and may involve pain, postsurgical inflammation, personnel disturbances, and heightened awareness in unfamiliar environments. 1 Additionally, general anesthesia may contribute to postoperative sleep impairments, which likely result from circadian rhythm shifts as controlled by the body’s hypothalamic SCN, or “master clock.” 2,8,12 Through a gamma-aminobutyric acid (GABA)-mediated inhibitory effect, propofol has been shown to impair circadian rhythm generation and decrease endogenous melatonin secretion. 2,8,13 It has also been shown that the neural oscillatory (electroencephalogram) dynamics produced by medication-induced activation of GABAergic neurons differ from those produced by natural sleep.…”
Section: Discussionmentioning
confidence: 99%
“…1 Additionally, general anesthesia may contribute to postoperative sleep impairments, which likely result from circadian rhythm shifts as controlled by the body’s hypothalamic SCN, or “master clock.” 2,8,12 Through a gamma-aminobutyric acid (GABA)-mediated inhibitory effect, propofol has been shown to impair circadian rhythm generation and decrease endogenous melatonin secretion. 2,8,13 It has also been shown that the neural oscillatory (electroencephalogram) dynamics produced by medication-induced activation of GABAergic neurons differ from those produced by natural sleep. 14 Therefore, it has been emphasized that despite phenotypic similarities, sleep and anesthesia do not share identical biochemical mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in a shift of the diurnal rhythm, with the onset of melatonin secretion occurring at an earlier or later point in the day. Furthermore, observational studies in humans have also shown delayed melatonin secretion and glucocorticoid release [ 23 ]. The potential disruption of the circadian timing system resulting from sleep irregularity during anesthesia may have a negative impact on human health and may hinder an individual’s ability to recover from surgery [ 24 ].…”
Section: Discussionmentioning
confidence: 99%